2023
DOI: 10.1111/btp.13239
|View full text |Cite
|
Sign up to set email alerts
|

Cactus height increases the modularity of a plant–frugivore network in the Caatinga dry forest

Abstract: Cacti fruits are key resources to many frugivorous animals in Neotropical arid and semiarid regions. However, most studies have focused on a particular animal group or cacti species, but few have explored the overall interactions of such species at the community level. Here we monitored frugivory on five cacti species using camera traps that sampled diurnal and nocturnal interactions. We investigated the structure of interactions with bird, mammal, and reptile frugivores in the Brazilian Caatinga dry forest. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…As EOS is the main selective force for masting ( Kelly and Sork, 2002 ), the close correlation between adult plant height and mast seeding intensity implies that increased plant height may also provide EOS through either enhancing pollination efficiency and/or increasing satiation of seed predators. Strong correlations between plant height and flower number ( Gomez, 2003 ; Trunschke et al., 2017 ), as well as increased attraction of pollinators, pollination success, and modularity of frugivorous network with plant height have been well observed ( Klinkhamer et al., 1989 ; Weber and Kolb, 2013 ; Dupont et al., 2014 ; Paixão et al., 2023 ), which are important for enhancing pollination efficiency. Evidence has shown that increased plant height significantly promotes pollen dispersal and then strongly increases pollination success ( Friedman and Barrett, 2009 , 2011 ; Harder and Johnson, 2009 ; Sletvold et al., 2010 ; Aljiboury and Friedman, 2022 ), which also provides EOS.…”
Section: Discussionmentioning
confidence: 99%
“…As EOS is the main selective force for masting ( Kelly and Sork, 2002 ), the close correlation between adult plant height and mast seeding intensity implies that increased plant height may also provide EOS through either enhancing pollination efficiency and/or increasing satiation of seed predators. Strong correlations between plant height and flower number ( Gomez, 2003 ; Trunschke et al., 2017 ), as well as increased attraction of pollinators, pollination success, and modularity of frugivorous network with plant height have been well observed ( Klinkhamer et al., 1989 ; Weber and Kolb, 2013 ; Dupont et al., 2014 ; Paixão et al., 2023 ), which are important for enhancing pollination efficiency. Evidence has shown that increased plant height significantly promotes pollen dispersal and then strongly increases pollination success ( Friedman and Barrett, 2009 , 2011 ; Harder and Johnson, 2009 ; Sletvold et al., 2010 ; Aljiboury and Friedman, 2022 ), which also provides EOS.…”
Section: Discussionmentioning
confidence: 99%